Step
*
1
1
2
of Lemma
es-interface-sum-le-interface
1. Info : Type
2. es : EO+(Info)
3. X : EClass(ℤ)
4. e : E
5. ↑e ∈b le(X)
6. ¬↑e ∈b X
⊢ if e ∈b X then if e ∈b prior(X) then Σ≤prior(X)(e)(X) else 0 fi  + X(e)
if e ∈b prior(X) then Σ≤prior(X)(e)(X)
else 0
fi 
= Σ≤prior(X)(e)(X)
∈ ℤ
BY
{ RepeatFor 2 ((SplitOnConclITE THEN Auto)⋅)⋅ }
1
1. Info : Type
2. es : EO+(Info)
3. X : EClass(ℤ)
4. e : E
5. ↑e ∈b le(X)
6. ¬↑e ∈b X
7. ¬↑e ∈b X
8. ↑e ∈b prior(X)
⊢ prior(X)(e) ∈ E
2
.....falsecase..... 
1. Info : Type
2. es : EO+(Info)
3. X : EClass(ℤ)
4. e : E
5. ↑e ∈b le(X)
6. ¬↑e ∈b X
7. ¬↑e ∈b X
8. ¬↑e ∈b prior(X)
⊢ 0 = Σ≤prior(X)(e)(X) ∈ ℤ
Latex:
Latex:
1.  Info  :  Type
2.  es  :  EO+(Info)
3.  X  :  EClass(\mBbbZ{})
4.  e  :  E
5.  \muparrow{}e  \mmember{}\msubb{}  le(X)
6.  \mneg{}\muparrow{}e  \mmember{}\msubb{}  X
\mvdash{}  if  e  \mmember{}\msubb{}  X  then  if  e  \mmember{}\msubb{}  prior(X)  then  \mSigma{}\mleq{}prior(X)(e)(X)  else  0  fi    +  X(e)
if  e  \mmember{}\msubb{}  prior(X)  then  \mSigma{}\mleq{}prior(X)(e)(X)
else  0
fi 
=  \mSigma{}\mleq{}prior(X)(e)(X)
By
Latex:
RepeatFor  2  ((SplitOnConclITE  THEN  Auto)\mcdot{})\mcdot{}
Home
Index